The egalitarian value of counterfeit goods: Purchasing counterfeit luxury goods to address income inequality - Liu, Jingshi (Joyce); Wakeman, S. Wiley; Norton, Michael I. (Journal of Consumer Psychology, 2025)
AbstractThe present research demonstrates a novel driver of the growing demand for counterfeit luxury goods: perceptions of income inequality. Across five studies, using different samples and counterfeit luxury goods, we find that as perceptions of income inequality increase, consumers value counterfeit luxury products for their “egalitarian value”—a value associated with counterfeits' perceived ability to restore equality in society. Consumers perceive both public and private counterfeit luxury goods to have egalitarian value, suggesting that their value manifests itself beyond consumers' attempts to signal status via consumption. Moreover, the egalitarian value increases consumers' motivation to purchase counterfeit luxury goods beyond their hedonic, utilitarian, economic, or status signaling value. Finally, the positive effect of the egalitarian value of counterfeit luxury goods on purchase preference is greater among consumers who think equality is more desirable and attainable (i.e., those low in social dominance orientation). Our results outline one psychological mechanism underlying consumers' interests in counterfeit luxury goods, explaining how egalitarian value may link two important societal issues: growing income inequality and increased demand for counterfeits.